How do individual farmers' objectives influence the evaluation of rangeland management strategies under a variable climate?. Issue 2 (12th February 2014) - Jakoby, Oliver; Quaas, Martin F.; Müller, Birgit; Baumgärtner, Stefan; Frank, Karin; Jones, Julia
Summary Management decisions by farmers are influenced by complex interrelations of ecological, economic and social factors. Of equal importance are the individual farmers' objectives. However, their relevance has been rarely considered in analyses of management decisions in farming systems. This study systematically analyses the role of farmers' objectives in their decision‐making under various climatic conditions, with dryland grazing systems as a case study. We develop a generic ecological–economic simulation model to compare the performance of a range of fixed grazing strategies under two objectives: (i) maximizing expected utility under risk aversion and (ii) achieving stochastic viability ('safety first'). We investigate combined effects of several management components in rotational grazing systems and assess the robustness of the results under different climate scenarios. The two objectives considered have structurally different outcomes. The evaluation under the objective to maximize (risk averse) expected utility indicates a trade‐off between mean income and income variability under which farmers would choose one individually optimal management strategy depending on their risk preferences. In contrast, a whole set of strategies is viable under the safety‐first objective. Thus, it offers a solution space for decision support rather than selecting a single optimal strategy. Under both objectives, economically preferable strategies share common characteristics: short standing time, large paddock number and reasonably high stocking rate improve the efficiency of a farm enterprise in terms of higher mean income, lower variance, coverage of certain minimum income requirements while preserving pasture quality. Synthesis and applications. The outcomes of this study contribute to both management support at the farm scale and policy advice at the regional scale and beyond. An insight of practical relevance for individual farmers is that a strategy type with high‐intensity, short‐duration grazing management appears to be most robust under changing climate and economic conditions. Nevertheless, considering individual farmers' objectives is essential for determining the individually optimal strategy. Furthermore, for policymakers, we provide an approach to evaluate policy programmes governing farming activities in terms of effectiveness and implications (particularly side effects). The explicit consideration of the diversity of individual objectives is crucial for avoiding counterproductive incentives and improving sustainability of land‐use policies.